Hadith Criticism in Western Academia: Challenges and Opportunities - Rayhan Ahmad Khairullah; Eka Purnama; Rizzaldy Satria Wiwaha; Engkos Kosasih; Irwan Abdurrahman (al-Afkar, Journal For Islamic Studies, 2026)
This study aims to examine the development of hadith criticism among Western scholars by highlighting its challenges and opportunities for contemporary Islamic studies. This research discusses how early Western scholars such as Ignaz Goldziher and Joseph Schacht viewed hadith not as divine revelation but as a socio-political construction that emerged after the Prophet’s era, thus casting doubt on its authenticity and authority. This study employs a qualitative method with a library research approach. The primary sources consist of Western scholars’ works on hadith and the responses of contemporary Muslim scholars to them. The analysis is conducted using a descriptive-analytical method, describing the views of the Orientalists and analyzing their implications for modern hadith studies. Although Western hadith criticism raises doubts about the sources of Islamic law, it also provides significant opportunities for the development of contemporary hadith studies. Such criticism encourages Muslim scholars to strengthen classical methodologies with modern scientific approaches and opens space for cross-traditional academic dialogue. Through the integration of classical isnād criticism methods and modern historical approaches—as undertaken by contemporary Muslim scholars such as Jonathan A.C. Brown and Muhammad Mustafa al-A‘zami—hadith studies can now develop in a more comprehensive, objective, and contextual manner. Therefore, Western hadith criticism is not only a challenge to Islamic authority but also a means of reflection and methodological reinforcement in global hadith scholarship.